The human–grass–fire cycle: how people and invasives co-occur to drive fire regimes - Fusco, Emily J; Balch, Jennifer K; Mahood, Adam L; Nagy, R Chelsea; Syphard, Alexandra D; Bradley, Bethany A (Frontiers in ecology and the environment, 2022)
Invasive grass species can alter fire regimes, converting native terrestrial ecosystems into non-native, grass-dominated landscapes, creating a self-reinforcing cycle of increasing fire activity and flammable grass expansion. Analyses of this phenomenon tend to focus on the ecology and geography of the grass–fire cycle independent of human activities. Yet people introduce non-native grasses to new landscapes (eg via agriculture), facilitate their spread (eg via road networks), and are a primary source of ignition (eg via debris burning). We propose a new framework for this phenomenon that explicitly recognizes the important role of anthropogenic activities in the human–grass–fire cycle. We review links between land use and invasive species as well as ignitions, with a particular focus on the spatial and temporal co-occurrences of these activities to show that these two drivers of wildfires are inextricable. Finally, management strategies that could mitigate impacts are discussed.